Determinants of Financial Development - Huang, Y.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2011)
A PDF version of this book is available for free in open access via the OAPEN Library platform, www.oapen.org. This book examines the emergence of both financial markets and carbon markets, and provides an in-depth investigation on the fundamental determinants of financial development.
Keywords: Macroeconomics; Urban economics; Financial services industry; Environmental economics; Development economics; International economic relations; Macroeconomics and Monetary Economics; Urban Economics; Financial Services; Environmental Economics; Development Economics; International Political Economy$1 (B.s